COVID-19: The Significance of Platelets, Mitochondria, Vitamin D, Serotonin and the Gut Microbiota - Bókkon, István; Kapócs, Gábor; Vucskits, András; Erdöfi-Szabó, Attila; Vagedes, Jan; Scholkmann, Felix; Szöke, Henrik (Current Medicinal Chemistry, 2021)
We provide a brief review of the significance of platelets, mitochondria, vitamin D, serotonin, and the gut microbiome in COVID-19. We hypothesize that hyperactive platelets and mitochondrial dysfunction, as well as low vitamin D level, gut dysbiosis, and increased serum serotonin produced by enterochromaffin cells, may all represent important aspects in the pathophysiology of COVID-19.
Keywords: vitamin D